ADAPTIVE SCHEDULING OF AERO-ENGINE ASSEMBLY BASED ON Q-LEARNING IN KNOWLEDGEABLE MANUFACTURE - Yan, Hong-Sen; Jiang, Nan-Yun; Wang, Hao-Xiang (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
An adaptive optimization scheduling AQ (Assembly Q-learning) algorithm of knowledgeable manufacture is proposed for an aero-engine assembly line to address the scheduling of an aero-engine assembly workshop in an uncertain manufacture system, which combines the real-time feature of Q-learning with the self-adaptation feature of knowledgeable manufacture system. An adaptive scheduling model of aero-engine assembly based on Q-learning is developed for the purpose of minimizing earliness penalty and completion time cost. New production scheduling rules are proposed to deal with the aero-engine assembly scheduling problem. Addressing the characteristics of aero-engine assembly, four system-state features are defined, and a proper reward is designed as a reward function. Coherence of the reward function and the scheduling objective is proved by theorem. Simulation tests show that the developed algorithm is superior to other scheduling rules in various situations. Particularly, in the ever-changing assembling environment, better results are guaranteed by the desirable adaptivity of the proposed algorithm.